USING AUTHENTIC MATERIAL TO TEACH TRANSLATION TO ENGLISH DEPARTMENT STUDENTS - Apri Yayat Susendi; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2017)
This paper is written to discuss the teaching of Translation for the students of English Department Students. The difficulties of producing an accurate translation and the importance Teaching Translation to produce a good and understandable translation product are the points underlying this paper. Therefore, the authors use the Authentic materials to assist students in studying Translation and prepare candidates to face the real translation work as they become the translator later. The material discussed is an explanation of authentic materials and the procedure of teaching Translation using Authentic Materials. This learning strategy is expected to be useful for an English professor in the field of translation so that they can enrich the teaching of translation. It is also desirable to students in order to improve their skills in the English language text mengterjemahkan and increase the motivation to learn translation.USING AUTHENTIC MATERIAL TO TEACH TRANSLATION TO ENGLISH DEPARTMENT STUDENTS